2016
DOI: 10.4103/2278-0203.192113
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of digital panoramic radiographs used for implant site assessment

Abstract: Aims:This study is conducted to determine the amount of distortion of digital panoramic radiographs.Materials and Methods:Panoramic radiographs of all patients who received dental implants in the years 2012 and 2013 were selected from the records at the faculty of dentistry, King Abdulaziz University. Radiographs were analyzed using the R4 Kodak Software for linear measurements of implants length and width. The measurements were compared to the actual size of the implant, and the amount of distortion was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…OPGs showed the greatest measurement deviation from the actual dimensions of implant. It showed magnification in the radiographic length compared to the actual size by 2.74mm, that is in concordance with the finding of the previous studies done by (Schropp, Stavropoulos et al 2009) where the difference mean was 1.25mm, but runs contrary to (Kayal 2016)'s study, where the radiographical length of the implant was examined and the measurements of the sample overall were decreased by 0.4 mm compared to the actual size. A study conducted by (Langlois Cde, Sampaio et al 2011) revealed that PAs on average, overestimated the actual measurements from dry hemi-mandible, while OPGs underestimated the real values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…OPGs showed the greatest measurement deviation from the actual dimensions of implant. It showed magnification in the radiographic length compared to the actual size by 2.74mm, that is in concordance with the finding of the previous studies done by (Schropp, Stavropoulos et al 2009) where the difference mean was 1.25mm, but runs contrary to (Kayal 2016)'s study, where the radiographical length of the implant was examined and the measurements of the sample overall were decreased by 0.4 mm compared to the actual size. A study conducted by (Langlois Cde, Sampaio et al 2011) revealed that PAs on average, overestimated the actual measurements from dry hemi-mandible, while OPGs underestimated the real values.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, there are some disadvantages which include inconstant imaging geometry, distortions that are inherent in intraoral radiography, and lack of cross-sectional information, which is important in implant site evaluation (Tyndall and Brooks 2000). In many cases, the radiographs along with proper clinical examination can be sufficient to determine the size and position of implants if distortion is accounted for (Kayal 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the panoramic radiograph is the standard radiograph exposed in the complete-arch rehabilitation, there are issues with standardization and distortion between each exposure. 17 Therefore, it can be argued that lack of detection of radiographic misfit by the authors, does not imply that additional samples of misfit would not exist. In addition, the presence of artifact within these radiographs could have produced false negative or false positives but the study investigators paid careful attention to rule out this error.…”
Section: Discussionmentioning
confidence: 93%
“…Most practitioners also take a secondary panoramic radiograph after 3 or 4 months of healing to study any early marginal bone loss around the implants. However, issues with standardization between two panoramic radiographs can be argued and present a major limitation to studies using radiographic analysis …”
mentioning
confidence: 99%
See 1 more Smart Citation